Antibiotic Activities To Staphylococcus aureus Phospholipase Of Aceh Cattle Preputium Isolate - Maryulia Dewi; Layli Adhayani; Zuraidawati Zuraidawati; Erina Erina (The International Journal of Tropical Veterinary and Biomedical Research, 2019)
This study aimed to study the effect of antibiotic on phospholipase production of Staphylococcus aureus isolated from preputium of Aceh cattle. The parameters measured in this study were PzI of Staphylococcus aureus without any treatment, and PzI of S. aureus after being given antibiotics. The experiment was carried out by modifying the Samaranayake method on egg yolk agar media, incubated at 37 ° C for 48 hours, and the precipitation lines formed was measured. The antibiotics used were tetracycline, oxytetracycline and fosfomycin with concentrations of 10%, 20% and 30% (mg / mL, respectively). The results showed that phospholipase production of S. aureus isolated from preputium of Aceh cattle was suppressed, antibiotics were able to inhibit phospholipase production. However, the enzyme was still produced in positive category, with PzI = 0.287, the highest result was found in 30% tetracycline activity, which is equal to PzI = 0.341 and the lowest was in 10% fosfomycin which is equal to PzI = 0.332